Performance of red palm oil, sunflower oil and vegetable ghee during deep fat frying - Taufiq Ahmad,; Shaheen Atta,; Abdussattar,; Anwar Ahmad,; Saeed Ahmad Nagra, (Universiti Kebangsaan Malaysia, 2003)
Three types of fats, red palm oil (RPO), sunflower oil (SFO) and vegetable ghee (VC) were used for repeated deep fat frying of potato fillets (French fries) for 5 consecutive days @ 20 minutes per day at 190-200oC and then allowed to cool for 18 hours. This practice was repeated for 10 times. The test oils were evaluated for physical and chemical deterioration. The quality indices i.e. peroxide value (POV), free fatty acid (FFA), anisidine value (A V), iodine value (IV) and colour (OD at 420 nm) of the samples were measured. It was found that all the quality parameters significantly (p<0.05) increased as frying time was advanced, while a reverse trend regarding IV was observed in each test oil. However, colour was negatively correlated with PO V, FFA and A V but positively with IV in case of RPO.